The effect of regulatory quality on the nexus between foreign direct investment and bank stability in a dual banking system - Lubna Alzarooni; Mohammad Al-Shboul; Aktham Maghyereh (Cogent Business & Management, 2025)
This paper examines the influence of regulatory quality (RQ) on the link between foreign direct investment (FDI) and bank stability in Gulf Cooperation Council (GCC) countries. Through panel data analysis for 128 banks (Islamic and conventional) from the six GCC countries, the study reveals that FDI adversely affects bank stability of the GCC region; stability of Islamic banks shows a greater exposure to the adverse effect of FDI compared the stability of conventional banks. However, higher RQ weakens the adverse effects of FDI on the stability of banks in the GCC region. Islamic banks display a more significant role in allowing RQ to mitigate the detrimental effect of FDI on the stability of the overall banking system. This finding underscores the role of Islamic banks in stabilizing the GCC’s financial system. The study offers clear understandings for regulators, policymakers, and risk managers, emphasizing the need for careful regulatory quality management, particularly during increased foreign capital inflows to safeguard monetary and financial stability amidst FDI.